(5y + 3x)(8y - 1)
First, change the subtraction symbol to the addition symbol:
(5y + 3x)(8y + -1)
All together: 40y2 + 24xy + -5y + -3x
There are no like terms to combine, so we are done.
First: 5y × 8y = 40y2
Outer: 5y(-1) = -5y
Inner: 3x × 8y = 24xy
Last: 3x(-1) = -3x
40y2 + 24xy + -5y + -3x
Again, no like terms, so we are done!
First, change subtraction symbol to addition:
Combine like terms:
There is no subtraction, so we don't need to worry about adding the opposite.
Combine like term:
49x4 + 42x2 + 9
Make it rain.